Language Learning Strategies: A Cross Sectional Survey Of Vocational High School Students - Intan Pradita; Jethra Nuha Nindita (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
The use of language learning strategies might be influenced by many factors such as gender, background cultures, career orientation and learning settings. In vocational setting, career orientation become an issue that needs a concern. The choice of department as career orientation is suspected to affect different strategies in learning English. This study aimed to identify the language learning strategies employed by the vocational high school students and to find out the differences in strategy use between two majors. This study involved 95 students from automotive engineering and electrical engineering of vocational high school students. Strategies Inventory for Language Learning (SILL) questionnaire which was constructed by Oxford (1990) was used in this study. Six domains were included in this questionnaire: Memory, Cognitive, Compensatory, Metacognitive, Affective, and Social. There are 50 items with 5 likert points in data completion. To analyze the data, SPSS and Microsoft Excel were used by the researcher. Results showed that there was a difference (M=9.168) in language learning strategies use of electrical engineering and automotive engineering students. Furthermore the metacognitive strategy was the most used while the memory strategy was the least used by the students.